The Characteristics Patients at Risk of Violent Behavior - PH, Livana; Ar Ruhimat, Imroati Istibsyaroh; Kurian, Midhu; Suerni, Titik; Sujarwo, Sujarwo; Kandar, Kandar; Maya, Anita; Nugroho, Arief; Anggraeni, Rina; Indrayati, Novi; Nurnainah, Nurnainah (Jurnal Ners Widya Husada, 2019)
Violent behavior is a maladaptive response from anger. Violent behavioral responses that cannot be controlled by a client will have a negative impact on the client and others. The study aimed to determine the characteristics of patients at risk of violent behavior. This research was a quantitative research through descriptive analytic method. A sample of 40 patients with violent behavior were treated at RSJD Dr. Amino Gondohutomo, Central Java Province. Sampling was done using random sampling method. Data collection tool was a questionnaire. Research data were analyzed univariately using frequency distribution. The results showed that the majority of respondents aged 26-35 years, were male, and high school graduates.Â Keywords: characteristics, patients, risk of violent behavior